Just Come Along: Six Poems. (2nd January 2021) - Gong, Yam; Shea, James; Tse, Dorothy
Abstract : This selection of Yam Gong's poems demonstrates his signature style, which includes mixing colloquial language (Cantonese) and everyday life with a philosophical acuity, direct address with paradox, and various lexical registers, such as dialogue, idioms, prayers, slang, and song lyrics. Yam Gong also writes with an internationalist outlook, using allusions to world literature, international news reports, and foreign languages in his work. His poem "Méditation, " for instance, refers to Jules Massenet's opera Thaïs and recasts the story of a fourth century Alexandrian courtesan in a Hong Kong setting. These poems are from Yam Gong's book And So Moving a Stone You Look at Festival Lights along the Street (2010).